2022
DOI: 10.1097/hjh.0000000000003194
|View full text |Cite
|
Sign up to set email alerts
|

Practical guide for the management of hypertensive disorders during pregnancy

Abstract: Hypertensive disorders of pregnancy, including gestational hypertension, preeclampsia, and eclampsia, are a worldwide health problem. Hypertensive disorders of pregnancy affect more than 10% of pregnancies and are associated with increased mortality and morbidity for both mother and fetus. Although patients' outcomes and family's experience will always be the primary concern regarding hypertensive complications during pregnancy, the economic aspect of this disease is also worth noting. Compared with normotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Hypertension during pregnancy is a major contributor to maternal and perinatal mortality 10 , 11 . We found that women with preeclampsia/eclampsia had a higher risk of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension during pregnancy is a major contributor to maternal and perinatal mortality 10 , 11 . We found that women with preeclampsia/eclampsia had a higher risk of cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to evaluate the ability to define the risk of developing preeclampsia by a screening test carried out in the first trimester (between 11 + 0 and 13 + 6 weeks of gestational age). The calculation of the risk is the result of the association of risk factors such as nulliparity, Afro-Caribbean ethnicity, BMI ≥ 30, chronic maternal hypertension, obstetric history, positive family history of PE, positive obstetric history of intrauterine fetal death (IUFD), or intrauterine growth restriction (IUGR), serum levels of PAPP-A (Pregnancy-Associated Plasma Protein A) and PlGF (Placental Growth Factor), ultrasound measurement of the pulsatility index of uterine arteries (PI), and mean arterial pressure (MAP) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%